Dedicatorias de afecto y resistencia en la biblioteca de Consuelo Berges (Altre Modernità, 2019)
The personal library of the writer Consuelo Berges, one of the most unique modern women writers, has a peculiarity: that of being a library in its majority of books written by women and that those copies are dedicated by their authors. The careful review and reading of these personal and autograph dedications allows us tracing the formation and evolution of a network of women  friends, almost all Latin American and Spanish writers, modern, free, and anti-fascist whose lives were thrown from their logical trajectory by the irruption of the twentieth century totalitarianisms. In this text, we have reconstructed and explored this transatlantic connection of women through their voluntary and involuntary itineraries outlined in those personal dedications of the copies that arrived, sent by their authors, to the house of Consuelo Berges, exiled inside Spain, during the harsh repression of the Franco regime. Those contacts between them, that crossed oceans, those expressions of affection expressed in the dedications of their books, we believe that were an engine and an impulse for the creation and even the survival, often in isolation, of this generation of women, in this case Latin American and Spanish, which we know as modern.